Evolution of Inter-Community Boundaries in Africa - Adejuyigbe, Omolade (Cahiers de géographie du Québec, 1974)
Amodel of the evolution of inter-community boundaries in Africa is presented. It is assumed that adjacent communities have different cores from which they progressively explore and interact in the frontier between them. The boundary is not fixed before there is effective occupation of the frontier and its evolution can be visualized in different stages : (i) expansion stage when the communities spread out from their different core areas ; (ii) contact stage when explorers and migrants come against physical or human hinderances to their expansion ; (iii) stabilization stage when each side lays exclusive claim to parts of the frontier from which it seeks to exclude the other. Attempt to exclude others may lead to conflicts on rights to sections of the frontier ; (iv) allocation stage when adjacent members of different communities resolve disputes arising from stabilisation and agree on the boundary between them; (v) delimitation stage when the entire length of the boundary between two communities is agreed upon and defined ; (vi) demarcation stage when the boundary is surveyed and marked ; (vii) administration stage during which the boundary is periodically supervised. Examples of real situations in Western Nigeria are used to illustrate each stage of the model.